Sonographic measurement of Achilles tendon thickness in seronegative spondyloarthropathies - (:unkn) unknown (My University, 2014)
Amaç: Spondiloartropati (SpA) hastalarında ultrason (US) kullanarak Aşil tendon kalınlığını belirlemede en iyi eşik değerini tanımlamak ve literatürde kullanılan farklı eşik değerleri ile karşılaştırarak tanısal yararlılığını değerlendirmek. Materyal ve Metot: Yüz bir birey (55 SpA hastası ve 46 yaş ve vücut kitle indeksi (BMI) eşleştirilmiş sağlıklı kontroller (SK)) incelendi. US, MyLab70 US sistemi (Esaote Biomedica, Cenova, İtalya) ile lineer prob (6-18 MHz) kullanılarak yapıldı. Her Aşil entezi için 3 görüntü saklandı ve longitudinal medyan taramada Aşil tendonunun kalkaneus kemiği içine girmiş derin kenarı seviyesinde entezin anteroposterior kalınlığı ölçüldü. Her cinsiyet için en iyi eşik değeri ROC eğrisi analizi ile belirlendi ve literatürdeki diğer eşik değerleri ile karşılaştırıldı: 1) Her iki cinsiyet için 5.29 mm ve 2) Kadınlar için 5.5 mm ve erkekler için 6.2 mm. Eşik değerlerini aşan ölçüm sayısı ve sensitivite (SE), spesifisite (SP), pozitif (PPD) ve negatif (NPD) prediktif değerleri hesaplandı. Bulgular: Cinsiyetler arasında (ortalama±SS: erkeklerde 4.6±0.7 mm ve kadınlarda 4.0±0.8 mm, p<0.00) ve SpA hastaları ile SK arasında (ortalama±SS: SpA hastalarında 4.4±0.8 mm ve SK'de 4.0±0.8 mm, p<0.001) Aşil entezi kalınlığı açısından anlamlı bir fark gözlendi. ROC eğrisi analizi en iyi eşik değerinin kadınlar için 3.7 mm ve erkekler için 4.8 mm olduğunu gösterdi (SE: %43-70, SP: %59-85, PPD: %66-79, NPD: %54-63). Daha önce rapor edilmiş eşik değerler yüksek SP (%91-98) fakat çok düşük SE'ye (%2-11) sahip olduğu bulundu. Sonuç: Aşil tendon kalınlığı cinsiyetler arasında farklılık gösterir; bu sebeple, cinsiyete spesifik normal değerlere başvurmak çok önemlidir. Yüksek eşik değerleri, daha önce de belirtildiği gibi, bu çalışmada çok düşük SE değeri gösterdi. Aşil entez kalınlaşması SpA hastalarında entezit tarama amacıyla kullanıldığında daha düşük bir eşik değeri daha yüksek bir SE'ye ve kısmen daha kötü SP değerine ve PPD ve NPD'ye sahiptir.

Objective: To define the best cut-off value for identifying Achilles tendon thickening using ultrasound (US) in patients with spondyloarthropathies (SpA) and to assess its diagnostic utility in comparison with different cut-off values used in the literature.Material and Methods: One-hundred and one subjects (55 SpA patients and 46 age and body mass index ((BMI)-matched healthy controls (HC)) were investigated. US was performed using a MyLab70 US system (Esaote Biomedica, Genoa, Italy) with a linear probe (6-18 MHz). Three images per Achilles enthesis were stored and the antero-posterior thickness of the enthesis was measured at the level of the Achilles tendon deeper margin insertion into the calcaneal bone on the longitudinal median scan. The best cut-off value for each gender was determined by ROC curve analysis and compared to the other cut-off values in the literature: 1) 5.29 mm for both genders, and 2) 5.5 mm for females and 6.2 mm for males. The number of measurements exceeding the cut-off values as well as sensitivity (SE), specificity (SP), positive (PPV) and negative (NPV) predictive values were calculated. Results: A significant difference was observed for Achilles enthesis thickness between genders (mean±SD: 4.6±0.7 mm in males vs. 4.0±0.8 mm in females, p<0.00) and between SpA patients and HC (mean±SD: 4.4±0.8 mm in SpA patients vs. 4.0±0.8 mm in HC, p<0.001). The ROC curve analysis revealed the best cut-off value to be 3.7 mm for females and 4.8 mm for males (SE: 43-70%, SP: 59-85%, PPV: 66-79%, NPV: 54-63%). Previously reported cut-off values were found to have high SP (91-98%) but very low SE (2-11%).Conclusion: Achilles tendon thickness differs between genders; thus, it is crucial to refer to normal values that are specific for gender. High cut-off values, as previously suggested, showed very low SE in the current study. When Achilles enthesis thickening is used for the purpose of screening enthesitis in SpA patients, a lower cut-off value has a higher SE with slightly worse SP, PPV and NPVs
Seronegatif spondiloartropatide Aşil tendon kalınlığının sonografik ölçümü
Keywords: Romatoloji